The bare minimum: satisfaction of sustainable development goal Target 6.2 by sanitation provisions in institutions of higher learning in Tigania West, Meru County - Okowa, Jesse Macintosh; Walubuka, Elijah; Munene, Halldess (African Journal of Science, Technology and Social Sciences, 2025)
Separation of human excreta from further contact with the environment has drawn universal attention through the SDGs which approach the provision of safely managed sanitation on SDG 6. Open defecation is the least sanitary option of waste elimination while safely managed sanitation where the waste is contained and treated/disposed is the most sanitary approach. As of 2020 the African population reached 1.3billion with 1.039billion lacking basic sanitation and 208million engaged in open defecation, 27% of the people had safely managed sanitation outside institutions. In Kenya, urban coverage of basic sanitation for 2015 – 2022 was 30% while safely managed sanitation was absent in the same area. Meanwhile, rural coverage of safely managed sanitation held at 25% with 2% coverage for basic sanitation. Thus, there was a demand to visualize the status of sanitation in vulnerable communities as the SDG window neared its end. A closed ended structured questionnaire to be self-filled was developed looking to assess the fulfillment of SDG target 6.2 by non-resident student housing and proportionately distributed to all institutions of higher learning in Tigania West targeting only non-resident students. Data analysis was performed by the principal investigator through categorization and comparison against real world statistics and targets as outlined by the Joint Monitoring Program. Findings indicated provisions were mainly shared with hand wash sinks largely missing. Dissatisfaction was higher with adequacy and availability of the sanitation provisions more than access to the provisions. This preempted the unsettling reality that the goals would not be actualized and that most people would be left behind on the continent. Such as it were, the study recommended for the actualization of targets, that sanitation provision be pursued over sustained blaming the vulnerable population for not engaging in practices beyond their reach.